Job Insecurity, Grit and Work Engagement in The Hospitality Industry During Covid-19 - Laila Meiliyandrie Indah Wardani; Jesi Oktavia Agustin Werinusa; Istiqomah Istiqomah; Mohammad Reevany Bustami (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This research was conducted to identify the influence of job insecurity and grit toward work engagement on 276 hospitality employees during the COVID-19 pandemic. It consisted of 81 male respondents and 195 female respondents. The sampling technique used was the purposive sampling technique, which has specific criteria. Those criteria are hospitality workers in hotels, the food and beverage industry, administration, marketing, travel, transportation, and housekeeping companies in Jakarta. This research used three measurement tools, namely, the Utrecht Work Engagement Scale (17 items; a = .856), the Job Insecurity Scale (9 items; a = .887), and the Grit Scale (12 items; a = .797). Multiple linear regression was used as a data analysis method. The findings indicated that during the COVID-19 pandemic, job insecurity and grit had an impact on the level of work engagement among hospitality employees. Job insecurity and grit both significantly affect how motivated people are at work in the hospitality industry. Employees’ job insecurity and grit have a positive relationship that can raise the value of work engagement. Therefore, decreasing job insecurity calls for high levels of grit and work engagement to keep employee positions within the organization. The strongest correlation was found between the dimensions of grit (perseverance of effort) and work engagement (dedication). Unlike this research, which was conducted on hospitality workers, the previous research was conducted on general workers. They expected the best performance, including maintaining a friendly smile and offering the best service in all circumstances while the pandemic was ongoing.